2015
DOI: 10.1515/aicue-2015-0007
|View full text |Cite
|
Sign up to set email alerts
|

Determinants Of Bank’s Profitability In EU15

Abstract: In this paper we analyse determinants of bank profitability of EU15 banking systems for the period 2001-2011. We use as proxy for banks profitability the return on average assets (ROAA), the return on average equity (ROAE) and net interest margin (NIM). We also measure the impact of the first and the largest wave of enlargement (10 new members in 2004) on EU15 bank profitability, introducing a dummy variable. The contribution of this paper for the empirical literature is that there are no other studies that de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
34
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 10 publications
7
34
0
2
Order By: Relevance
“…In addition, large banks are usually more profitable (e.g. Căpraru and Ihnatov, 2015) and do not have liquidityprofitability trade-off as they rather adopt borrowed liquidity strategy or balanced liquidity management strategy than the asset conversion strategy (Rose and Hudgins, 2013), what is empirically confirmed for the Croatian banking sector in the pre-crisis period (Kundid Novokmet et al, 2016). But besides availability of the interbank market funds, attention should be payed to affordability of the short-term liabilities as it is confirmed that over the period 2003-2008 Croatian banks profitability was more determined with the interest costs on received loans than the interest costs on received deposits (Kundid, 2014).…”
Section: Source: Authors' Calculation Figure No 2 -The Mean Values Omentioning
confidence: 95%
“…In addition, large banks are usually more profitable (e.g. Căpraru and Ihnatov, 2015) and do not have liquidityprofitability trade-off as they rather adopt borrowed liquidity strategy or balanced liquidity management strategy than the asset conversion strategy (Rose and Hudgins, 2013), what is empirically confirmed for the Croatian banking sector in the pre-crisis period (Kundid Novokmet et al, 2016). But besides availability of the interbank market funds, attention should be payed to affordability of the short-term liabilities as it is confirmed that over the period 2003-2008 Croatian banks profitability was more determined with the interest costs on received loans than the interest costs on received deposits (Kundid, 2014).…”
Section: Source: Authors' Calculation Figure No 2 -The Mean Values Omentioning
confidence: 95%
“…The good performance of banks is not isolated to South Africa, it is a general phenomenon across geographies, including in emerging Europe where there was a substantial increase in total assets as a percentage of GDP (Anayiotos, Totoyan and Vamvakidis, 2010). As the proportion of assets to GDP grows, growth in non-interest revenue is encouraged, leading to better earnings stability (Albertazzi & Gambacorta, 2009, Capraru & Ihnatov, 2015. At business level, cost and profitability are major determinants of financial performance, hence the variety of studies that have been conducted to understand the underlying drivers of these variables (Shahwan & Hassan, 2013).…”
Section: Overviewmentioning
confidence: 99%
“…These can range from the heterogeneous nature of banks to economic and business cycles, bank size, financial risk, regulation and regulatory capital, as well as ownership, collectively called "other market factors" (Ariff & Can, 2008;Isik & Hassan, 2002;Mathuva, 2009). These elements can be categorised into two broad categories: bank-specific internal factors and external factors (Capraru & Ihnatov, 2015;Forster & Shaffer, 2005;Pasiouras & Kosmidou, 2007).…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In the majority of studies, the effect of the sector is expressed by the variables of the H. H. Index (Herfindahl Index), as well as the percentage of the overall sector held by the three or five largest banks at an assets level (CR-3, CR-5). The Market Power Hypothesis is included in the industry framework and recognizes that, only banking institutions with large market share and well diversified products, are in position to apply their leadership influence in order to increase their monopoly / oligopoly profits (non-competitive products) (Berger, 1995;Kosmidou, 2008;Athanasoglou et al, 2005;Samy Ben Naceur, 2003;Capraru, 2015;Hoffmann, 2011;Petria et al, 2013;.…”
Section: • Industry Specific Determinantsmentioning
confidence: 99%